Blockchain-enabled access control to prevent cyber attacks in IoT: Systematic literature review - Singh, Rinki; Kukreja, Deepika; Sharma, Deepak Kumar (Frontiers in Big Data, 2023)
Internet of Things (IoT) enables communication among objects in order to collect information and draw decisions to improve quality of life. There are several unresolved security and privacy concerns in IoT due to multiple resource constraint devices which leads to various cyber-attacks. The conventional access control techniques depend on a central authority, which further poses privacy and scalability issues in IoT. Various problems with access control in IoT can be resolved to prevent various cyber-attacks by using the decentralization and immutability properties of the blockchain. This paper explores the current research trends about blockchain-enabled secure access control mechanisms and also identifies its applicability in creating reliable access control solutions for IoT. Basic properties of blockchain, like decentralization, auditability, transparency, and immutability are the propulsion that provides integrity and security disregarding the participation of an external entity. At first, the application of blockchain was only for cryptocurrencies but with the introduction of Ethereum, which allows to write and execute smart contracts, applications other than cryptocurrencies are being created. As various research papers are available using different types of blockchain for creating secure access control solutions for IoT, this article intends to find and examine such primary researches, as well as come up with a systematic review of various findings. This study perceives the most frequently utilized blockchain for creating blockchain based access control solutions to prevent various cyber-attacks and also discusses about the improvement in access control mechanisms by using blockchain along with smart contracts in IoT.The study also discusses the obstacles in building decentralized access control solutions for IoT systems, as well as future research areas. For new researchers, this publication is a nice place to start and a strong reference point.